The synthesis of the pentacyclic carbon framework of the PF1270 family of natural products - Sanchez, Michelle A., author; Williams, Robert M., advisor; Kennan, Alan, committee member; Rovis, Tomislav, committee member; Levinger, Nancy, committee member; Crick, Dean, committee member (Colorado State University. Libraries, 2014)
The PF1270 family of natural products contains novel indole alkaloids that display interesting biological activity; the synthesis of these natural products and their analogs could lead to the discovery of novel therapeutics. Discussed herein is the synthesis of the complete pentacyclic carbon framework of the PF1270s, accomplished through a key intermolecular Diels-Alder reaction. Other highlights of the synthesis include an acid catalyzed opening lactim ether at a late stage, and a particularly difficult decarboxylation promoted by diphenylphosphoryl azide.